Imaging Findings of Pancreatic Solid Pseudopapillary Neoplasm with High-Grade Malignant Transformation: Focusing on DiffusionWeighted Imaging and Normalized Apparent Diffusion Coefficient Values - Ka Ram Kang; Ok Ran Shin; Su Lim Lee; Young Mi Ku (대한영상의학회지, 2018)
Solid pseudopapillary neoplasm (SPN) of the pancreas is an uncommon neoplasm characterized by low-grade malignant potential and uncertain histogenesis, and usually afflicts relatively young women. The tumors typically manifest as well-marginated, mixed density lesions consisting of a solid peripheral and central cystic component in conjunction with hemorrhagic foci. SPN with apparent high-grade malignant transformation is a rare histologic variant. Herein, we report a rare case of SPN with high-grade malignant transformation diagnosed in a 75-year-old female, with emphasis on differential diagnoses and role of normalized ADC values. SPN with malignant transformation should be included in the differential diagnosis in cases of mixed solid and cystic masses with hemorrhagic components, irregular margin and lower normalized apparent diffusion coefficient (ADC) values in an elderly female patient, as was the case discussed below.